Description of Psychosocial Problems in Taruna Muda Politeknik Ilmu Permasyarakatan in the Study from Home - Henri Yudiantoro (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
Corona Virus-19 Disease (Covid-19) disease continues to increase from day to day days various attempts were made to prevent the further spread of this pandemic, wrong only policy began to be applied was the policy of enforcing the Study of Home for students and students in Indonesia. Impact of Covid-19 causes both physiologically and psychologically.To identify the effects of Covid-19 in pshycological condition in Taruna who Study from Home, regarding the description of psychosocial problems in young cadets (new students in Politeknik Ilmu Permasyarakatan Indonesia). This type of research is a descriptive study with a cross-sectional design, with using online survey research design and conducted in May 2020 on young cadets of the Politeknik Ilmu Permasyarakatan Indonesia. The study population was all young cadets active Politeknik Ilmu Permasyarakatan Indonesia class of 2019 which was arrested 309 people. Sample in this research uses simple random sampling technique. Minimal sample in this study obtained by using Lemeshow, as many as 84 people and the analysis use distribution frequensi method.From the research conducted obtained 69 cadets (82.1%) using anxiety minimum, 11 cadets (13.1%) improved mild anxiety, 3 cadets (3.6%) improved anxiety moderate, and as many as 1 cadet (1.2%) improve severe anxiety.With the application of Home Studies in the midset of the Covid-19 pandemic, this is challenging found in young cadets, so it needs to be followed up to prevent the impact worse, psychosocial, more severe later on.